International Diplomacy Policy on the Iran–United States War (2025–2026) from the Perspective of Siyasah Harbiyah: International Diplomacy Policy on the Iran–United States War (2025–2026) from the Perspective of Siyasah Harbiyah - Rojaya Marbun; Syaiful Amri (PENA LAW: International Journal of Law, 2026)
This research is motivated by the escalation of geopolitical tensions between Iran and the United States during the 2025–2026 period. This conflict peaked with Iran's implementation of a maritime blockade of the Strait of Hormuz. The closure of this global energy route significantly impacted the international economy, including threats of inflation and a surge in energy subsidies, particularly in Indonesia. This study aims to dissect the dynamics of Iran's foreign policy changes and multilateral diplomatic responses from a Siyasah (Islamic politics) perspective. Using a normative juridical method that is qualitative-descriptive with a case approach, data were collected through a literature review of primary, secondary, and tertiary legal materials, such as the Qur'an, Hadith, classical fiqh literature, and relevant regulatory documents. The theory of Siyasah Dauliyah serves as the macro framework for international relations, while Siyasah Harbiyah functions as a specific analytical tool for armed crisis conditions. The results show that Iran's initial blockade of the Strait of Hormuz was a legitimate form of asymmetric defense (al-difa') when its state sovereignty was threatened. However, between April and May 2026, the Iranian government engaged in political ijtihad by gradually reopening access to the strait through envoy channels (al-sifarah) mediated by neutral countries such as Oman and Qatar. This de-escalation was triggered by multilateral diplomatic pressure from forums such as the OIC and the UN. The study concludes that the flexibility of Iran's policy, shifting from military confrontation to peaceful accommodation, is a clear manifestation of the enforcement of contemporary Siyasah Dauliyah and Siyasah Harbiyah strategies to achieve shared economic benefit (maslahah ammah) and prevent wider global harm.